PID controller design for DC motor using matlab application - Mohamed Farid, Mohamed Faruq (2008)
This project is a simulation and experimental investigation into the development of PID controller using MATLAB/SIMULINK software. The simulation development of the PID controller with the mathematical model of DC motor is done using Ziegler–Nichols method and trial and error method. The PID parameter is to be tested with an actual motor also with the PID controller inMATLAB/SIMULINK software. In order to implement the PID controller from the software to the actual DC motor data acquisition is used. From the simulation and the experiment, the result performance of the PID controller is compared in term of response and the assessment is presented.